Navigating Toxic Parental Relationship: A Study of Attachment Theory in August Wilson’s Fences (Journal of the College of Education for Women, 2024)
August Wilson, in his play Fences, presents the father-son relationship as the character of the father stands for toxic parent. This paper investigates the intersection between attachment theory and the concept of toxic parental relationships in the play. Attachment theory divides into two sections: one is secure and the other is insecure, which divides into three patterns (avoidant, ambivalent, and disorganized). The aim of the study is to delve into the characters' attachment patterns and how they shape their interactions within the familial context. The study attempts to understand the dynamics of attachment between the protagonist, Troy Maxson, and his sons, Lyons and Cory, through an analysis of their relationship within themes of love, control, and generational trauma. Furthermore, the research examines the implications of these attachment patterns on familial conflicts and individual development. Through a nuanced exploration, it contributes to a deeper understanding of the complex interplay between attachment theory and the portrayal of toxic parental relationships in literary narratives.